Sistema para generar gráficas a partir de logs tcpdump usando hadoop - Cruz, Ángel (2009)
The size of the logs to be processed is relatively large, so we need a massive processing of these data, we use the schema for MapReduce through Hadoop Framework. A system that generates graphs from a processing and analyzing tcpdump logs. We analyzed the data to be processed by the system, there is a brief description of the format of logs and convert them. We propose the design of the solution, the tools we use to develop the system, it explains how MapReduce works phases in our solution. We detail the implementation and operation of the system described tests on Amazon Web services and the results obtained. Finally, we present the conclusions obtained with the development of the scheme MapReduce system.